Mental Health Policy in Brazil and Paraguay: symmetries and asymmetries / Política de saúde mental no Brasil e no Paraguai: simetrias e assimetrias (Argumentum, 2018)
This article presents and characterises the implementation of Mental Health Policy in Brazil and Paraguay based on Policy Cycle logic; Problem identification; forming the agenda; formulation; implementation and evaluation.  To achieve this objective a wide bibliographical review, documentary research and data content analysis were carried out.  The results of the research indicate that the implementation process in Brazil and Paraguay has gradually been consolidated across treatment networks and the Network of Psychosocial Care (RAPS), in the case of Brazil, and the Integrated Networks of Health Systems/Care Line in Mental Health (RISS) in Paraguay, presenting both symmetries and asymmetries apparent in the process of institutionalisation. Keywords: Implementation. Policy Cycle. Mental Health Policy. Brazil. Paraguay.